A cross-cultural validation of the Attention Questionnaire of Rehabilitated Athletes Returning to competition. (July 2020) - Conti, Cristiana; di Fronso, Selenia; Bertollo, Maurizio; Robazza, Claudio
Abstract: Objectives: To culturally adapt the Attention Questionnaire of Rehabilitated Athletes Returning to Competition (AQ-RARC) in the Italian language. Design: Cross-sectional study. Setting: Italian athletes. Participants: We recruited 324 athletes (215 men, 109 women) divided in two samples: 101 injured athletes returning to their first competition following injury, 223 non-injured athletes making their first competition of the regular season. Main outcome measures: The AQ-RARC-IT, the Psychobiosocial States Scale (PBS-ST), and a Concentration Disruption scale. Athletes completed the questionnaires at the end of their first competition. We investigated the construct validity, the internal consistency, and the concurrent validity of all measures. Results: A confirmatory factor analysis (CFA) supported the two-factor structure of the AQ-RARC-IT yielding acceptable fit indices, CFI = 0.930, TLI = 0.912, RMSEA (90% CI) = 0.100 (.076–.123), and SRMR = 0.082. Concurrent validity was evaluated through Pearson's correlation coefficients between measures. Correlations ranged in magnitude from weak to moderately high. Conclusions: Study findings showed satisfactory psychometric properties of the AQ-RARC-IT. The questionnaire can be used for clinical and research purposes. Highlights: Decreased attention or increased distractibility augment the risk of re-injury and sub-optimal performance. The AQ-RARC assesses selective attention of injured athletes returning to competition. Cross cultural investigations of the scale have not been previously conducted. Confirmatory Factor Analysis of the Italian version (AQ-RARC-IT) supported the two-factor structure.